Restorative Justice in Cases of Child Sexual Abuse by Children: Between Child Protection and the Enforcement of Justice - Permas Teti; Somawijaya Somawijaya; Budi Arta Atmaja (JUSTISI, 2026)
This study aims to evaluate the application of restorative justice in cases of child molestation by children, by analyzing its legal and ethical implications. The method used was empirical jurisprudence with an interdisciplinary approach that integrated law, social sciences, and psychology, with a descriptive analytical research specification. Data were obtained through field studies and literature reviews, then analyzed qualitatively. The novelty of this research lies in its specific examination of the legal and ethical implications of applying restorative justice in cases of child molestation by children, which have often been resolved through amicable agreements between parents without considering the best interests of the child victims. The findings of this research show that restorative justice has the potential to neglect the protection of victims and the enforcement of justice, as well as eliminate the legal responsibility of the child perpetrator. The conclusion of this study confirms that the application of restorative justice in cases of child molestation by children is not in line with applicable legal provisions and has the potential to cause injustice, so it is not appropriate to apply it given its serious impact on the psychological condition and future of the child victim.